Total compounds of Secondary Metabolites Soy-Yamghurt Formula and Nephropathy Effect in Male White Rats - Joni Tandi; Viani Anggi; Vidya Christin; Nur Ikhwan; Niluh Puspita Dewi; Magfiroh Magfiroh; Recky Patala; Tien Wahyu Handayani (Syarif Hidayatullah State Islamic University, 2022)
Complications of diabetes mellitus cause diabetic nephropathy. Soy-yamghurt is made from a combination of Banggai sweet potato juice and fermented soybean juice to be a functional food for diabetic nephropathy sufferers. This study aimed to analyze quantitatively the secondary metabolites contained in soy-yamghurt and to determine the effectiveness of soy-yamghurt in reducing urea and creatinine levels. This study used an experimental method with a total of 25 rats divided into 5 groups, namely normal control, negative control, soyyamghurt treatment group with a comparison of yam and soybean extract, namely F1(1:1), F2(1:2), and F3(2:1). The parameters observed were urea and creatinine levels on days 0, 7, 14, 21, and 28. The results obtained were the total levels of secondary metabolites of Alkaloid compounds F1 0.10% v/v, F2 0.01% v/v, and F3 0.01% (v/v), Flavonoid compounds F1 0.14% (v/v), F2 0.12% (v/v), F3 0.13% (v/v), Tanin compounds F1 0.27% (v/v), F2 0.26% (v/v), F3 0.14% (v/v) and saponins F1 1.15% (v/v), F2 1.22% (v/v), F3 1.25% (v/v). Administration of soy-yamghurt F2 was effective in lowering urea and creatinine levels. With an average value of 14.66 mg/dL urea and 0.40 mg/dL creatinine.